Spray Paint Activity Related With Volatile Organic Compounds (Vocs) : A Literature Review - Nor Hafeizah, Hassan; SAID, MD RADZAI; Leman, A. M (2012)
Currently, Industrial workers are exposed to contaminants and affect on occupational health at workplace. Spray painting activity is related with inhalation of Volatile Organic Compounds (VOCs) exposure. This paper highlight issues from the review of every angle of pointing activities and the relationship to VOCs. Painting activity can be divided into three (3) elements. (This includes the effect of painting activity, assessments and managing). Furthermore, worker exposure, effect and control of VOCs and a need of ventilation system will be discussed. The spray-painting activity is significantly related to VOCs exposure and will lead to occupational health diseases and sufficient ventilation systems should be applied.